Eagle owl Bubo bubo proximity can lower productivity of cliff-nesting peregrines Falco peregrinus - M. Brambilla; D. Rubolini; F. Guidali (Suomen lintutieteellinen yhdistys, 2006)
The Eagle Owl Bubo bubo is conventionally regarded as an important predator of smaller diurnal birds of prey. In this study, we analysed the relationships between Peregrine productivity and the proximity to Eagle Owl nests/cliffs in a cliff-nesting Peregrine Falco peregrinus population across the central pre-Alps of Italy and Switzerland over three breeding seasons. There was no effect of Eagle Owls on Peregrine productivity over the whole study area, whereas in a restricted sub-area, where both species occurred at higher densities, proximity to Eagle Owl nests/cliffs and syntopic co-occurrence of the two species at a given cliff complex resulted in lower Peregrine productivity. Eagle Owl effects at the wider scale were probably masked by other ecological and/or environmental features affecting reproductive success of the Peregrine, whereas these became evident when focusing on a more restricted and homogeneous area. Thus, our study suggests that Eagle Owls may affect population dynamics of diurnal raptors via an effect on productivity.